Myelinating Schwann cells and Netrin-1 control intra-nervous vascularization of the developing mouse sciatic nerve - Sonia Taïb; Noël Lamandé; Sabrina Martin; Fanny Coulpier; Piotr Topilko; Isabelle Brunet (eLife, 2022)
Peripheral nerves are vascularized by a dense network of blood vessels to guarantee their complex function. Despite the crucial role of vascularization to ensure nerve homeostasis and regeneration, the mechanisms governing nerve invasion by blood vessels remain poorly understood. We found, in mice, that the sciatic nerve invasion by blood vessels begins around embryonic day 16 and continues until birth. Interestingly, intra-nervous blood vessel density significantly decreases during post-natal period, starting from P10. We show that, while the axon guidance molecule Netrin-1 promotes nerve invasion by blood vessels via the endothelial receptor UNC5B during embryogenesis, myelinated Schwann cells negatively control intra-nervous vascularization during post-natal period.